1996
DOI: 10.2527/1996.7471711x
|View full text |Cite
|
Sign up to set email alerts
|

Serum and milk folates during the first two gestations and lactations in Romanov, Finnsheep, and Suffolk ewes.

Abstract: Concentrations of folates in serum and milk were determined during the first two parities in 7 Suffolk, 12 Finnsheep, and 15 Romanov ewes at 0 (mating), 60, 110, and 140 d of gestation and 1, 7, 14, 21, and 50 d of lactation. The number of lambs born at first and second parturitions was 1.38 +/- .13 and 1.71 +/- .13 for Suffolk, 2.00 +/- .32 and 2.33 +/- .57 for Finnsheep, and 2.67 +/- .24 and 3.20 +/- .22 for Romanov, respectively, and the concentration of folates at d 0 was 1.17 +/- .21, 1.87 +/- .19, and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
14
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
5
14
0
Order By: Relevance
“…Vitamin B 12 concentrations were unaffected (P 5 0.58) by choline and vitamin E supplementation; however, a significant time effect was observed after the second week of lactation, when B 12 levels started to increase in all groups. The folate trends we observed are broadly similar to those reported in Saanen goats (Ford et al, 1972) and also in ewes (Girard et al, 1996). In both these studies, plasma folate peaked around parturition.…”
Section: Resultssupporting
confidence: 77%
“…Vitamin B 12 concentrations were unaffected (P 5 0.58) by choline and vitamin E supplementation; however, a significant time effect was observed after the second week of lactation, when B 12 levels started to increase in all groups. The folate trends we observed are broadly similar to those reported in Saanen goats (Ford et al, 1972) and also in ewes (Girard et al, 1996). In both these studies, plasma folate peaked around parturition.…”
Section: Resultssupporting
confidence: 77%
“…In sheep, serum concentrations of folates decrease between mating and 60 d of gestation and increase before lambing time (Girard et al 1996), following a pattern similar to that observed in sows (Matte and Girard 1999). Moreover, the decrease in serum concentrations of folates observed between mating and 60 d of gestation is greater in prolific breeds (Girard et al 1996).…”
supporting
confidence: 62%
“…Moreover, the decrease in serum concentrations of folates observed between mating and 60 d of gestation is greater in prolific breeds (Girard et al 1996). These results suggest that the demand for folic acid might be increased during gestation in ewes.…”
mentioning
confidence: 73%
“…Moreover, genotypes of different prolificacy did not influence the response of plasma folates to supplementation. However, the prolific crossbred ewes used in this study had smaller litters than the prolific pure breeds studied by Girard et al (1996). Folic acid supplementation produced an overall increase in red cell folate concentration (Fig.…”
Section: Effect Of Dietary Supplements Of Folic Acid On Concentrationmentioning
confidence: 99%
“…In a previous study, Girard et al (1996) showed that, in the absence of folic acid supplementation, ewes of prolific breeds had higher plasma concentrations of folates than less prolific ewes (Romanov Finn Suffolk) at the time of mating and during gestation. In the present study, there were no differences in plasma folate concentrations between prolific and non-prolific ewes in the control group.…”
Section: Effect Of Dietary Supplements Of Folic Acid On Concentrationmentioning
confidence: 99%